APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE MANAGEMENT OF FOOD STORAGE AND LOGISTICS: https://doi.org/10.5281/zenodo.15443143 - Muftaydinov , Mansur (Journal of Contemporary World Studies, 2025)
This article explores the application and effectiveness of artificial intelligence (AI) technologies in the management of food storage and logistics processes. Modern global food supply systems require advanced technological solutions to ensure real-time monitoring, expiration tracking, waste reduction, and efficient distribution. The paper examines the role of AI-driven technologies, including machine learning, computer vision, smart sensors, and automated data analytics, in maintaining optimal storage conditions and improving decision-making across the supply chain. Furthermore, the study analyzes how AI enhances logistics by optimizing delivery routes, automating warehouse operations, and forecasting consumer demand. The findings demonstrate that widespread integration of AI technologies contributes to improved food safety, product quality preservation, and increased operational efficiency in food supply and logistics systems.